2019
DOI: 10.1155/2019/6798140
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors and Haematological Indexes of Inflammation in Paralympic Athletes with Different Motor Impairments

Abstract: Haematological indexes of both inflammation and platelet activation have been suggested as predictive markers of cardiovascular disease (CVD), which has high prevalence in Paralympic athletes (PA). Different mechanisms could play a role in increasing CVD risk in PA with spinal cord injury (PA-SCI), lower limb amputation (PA-LLA), or upper limb impairment (PA-ULI). We compared, in 4 groups of PA competing in power, intermittent (mixed metabolism), and endurance sports, Framingham Risk Score (FRS), metabolic syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…However, a high prevalence of ACVD-risk factors was even found both in a group of brazilian paralympic athletes (67 with physical and 12 with visual impairment), including 11 with SCI, 6 with lower limb deficiency, 27 with poliomyelitis sequelae, and 21 with cerebral palsy [33], and in 50 elite italian paralympic athletes competing in summer and winter games including athletes with SCI, lower limb amputation (n = 15), and upper limb impairments (n = 10) [34]. Also in the present study, the prevalence of ACVDrisk factors was considerably high, having about 2/3 of the sample at least 1 ACVD-risk factor, while 28% had 2 or more ACVD-risk factors, confirming that the prevalence of modifiable ACVD-risk factor in paralympic athletes with locomotor impairment is relevant, as already stated [33,34]. The comparison between paralympic athletes with SCI and those with other Health Conditions did not find any significant difference in both absolute values and prevalence of the modifiable ACVD-risk factors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, a high prevalence of ACVD-risk factors was even found both in a group of brazilian paralympic athletes (67 with physical and 12 with visual impairment), including 11 with SCI, 6 with lower limb deficiency, 27 with poliomyelitis sequelae, and 21 with cerebral palsy [33], and in 50 elite italian paralympic athletes competing in summer and winter games including athletes with SCI, lower limb amputation (n = 15), and upper limb impairments (n = 10) [34]. Also in the present study, the prevalence of ACVDrisk factors was considerably high, having about 2/3 of the sample at least 1 ACVD-risk factor, while 28% had 2 or more ACVD-risk factors, confirming that the prevalence of modifiable ACVD-risk factor in paralympic athletes with locomotor impairment is relevant, as already stated [33,34]. The comparison between paralympic athletes with SCI and those with other Health Conditions did not find any significant difference in both absolute values and prevalence of the modifiable ACVD-risk factors.…”
Section: Discussionmentioning
confidence: 95%
“…At our best knowledge, however, the relationship between aerobic fitness and cardiovascular risk reduction is debated in individuals with SCI with low cardiovascular fitness [27][28][29] and it has been only suggested but not demonstrated in Paralympic Athletes [30], even though sport has been repeatedly considered and used as one of the most effective ways to improve cardiovascular fitness and provide health benefits in people with SCI [31], lower limb amputation [32], and other health conditions [30]. Nevertheless, a Brazilian study [33] and a recent Italian study [34] found in different cohorts of Paralympic Athletes a high prevalence of ACVD-risk factors. In spite of a demonstrated increased energy expenditure [35,36] and its direct impact on VO 2peak [35], some paralympic athletes are still at high risk of developing ACVD.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle atrophy and increased sedentary time increase the risk of glucose intolerance, potentially leading to insulin resistance (17). Osteoporosis, oxidative stress, chronic systemic inflammation, reduced cardiovascular efficiency, dyslipidemia, and cardiovascular disease (CVD) risk are also elevated with a SCI (17). While physical activity can positively impact the aforementioned health concerns, CVD risk remains elevated in Paralympic athletes with a SCI (18).…”
Section: Physiological Considerations For Para-scimentioning
confidence: 99%
“…While physical activity can positively impact the aforementioned health concerns, CVD risk remains elevated in Paralympic athletes with a SCI (18). A more recent assessment comparing Paralympic athletes with an amputation vs. a SCI found that PARA-SCI with a high lesion SCI had a higher plateletderived cardiovascular risk as compared with those with an amputation, which the authors attributed to malnutrition (17).…”
Section: Physiological Considerations For Para-scimentioning
confidence: 99%
“…Although, among celiac individuals, chocolate consumers had a higher lymphocyte-to-monocyte ratio [11] and a lower neutrophil-to-lymphocyte ratio [12], two hematological indexes of inflammation [13], while no differences were observed between chocolate consumers and non-consumers in red blood cell count, mean corpuscular volume, and hemoglobin values [11], a nutrition or health claim should not be made if it is inconsistent with generally accepted nutrition and health principles or if it encourages or condones excessive consumption of any food or disparages good dietary practice [1]. The COMMISSION REGULATION (EU) No 488/2014 (amending Regulation (EC) No 1881/2006) as regards maximum levels of cadmium in foodstuffs reported the following: "Chocolate and cocoa powder sold to the final consumer can contain high levels of cadmium and are an important source of human exposure.…”
mentioning
confidence: 96%